Southwest trading - Paraiso, Arleen J.; Navarro, Angelina M. (1988.)
The said case is a typical problem among small scale garment manufacturers. This study intent to highlight the specific factors leading to such failure with a view of: 1. Recommending corrective measures in order to prevent total close of the shop or similar cases as stated in the preceeding pages. 2. Recommending initial actions to recover such business in the midst of failure.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade